Characteristics of Volatile Organic Compounds Emissions and Odor Impact in the Pharmaceutical Industry - Hongchao Zhao; Ying Cheng; Yanling Liu; Xiuyan Wang; Yuyan Wang; Shuai Wang; Taosheng Jin (Atmosphere)
Volatile Organic Compounds (VOCs) are not only essential precursors for the formation of ozone and PM2.5, but also hazardous to human health and responsible for unpleasant odors. The pharmaceutical industry has become an important industrial source of VOCs due to China’s large emissions and complex emission chains. In total, 245 VOCs samples were collected and analyzed from 11 typical pharmaceutical companies in Zibo City of the North China Plain, in order to investigate the VOCs emission characteristics and odor impacts. The emission factor for the pharmaceutical industry was 7.97 ± 8.21 g/kg pharmaceuticals, while the main emission links were chimney emissions, equipment sealing leakage, and so on. Finally, considering both purifying efficiency and economic benefits, the multistage absorption (AB) method is most effective for VOCs concentrations below 100 mg/m3, while UV photo-oxygenation combined with adsorption (UVA) is more suitable for concentrations below 300 mg/m3. The Regenerative Thermal Oxidizer (RTO), Catalytic Oxidizer (CO), and Condensation + Adsorption (CA) technologies demonstrated greater stability and efficiency, particularly in the treatment of complex organic pollutants, highlighting their advantages in both VOCs and odor removal at higher concentrations.